2016
DOI: 10.1111/zoj.12449
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an isogenic strain of the desiccation-sensitive tardigradeIsohypsibius myrops(Parachela, Eutardigrada) and its life history traits

Abstract: Tardigrades are aquatic micrometazoans found in various habitats. Many limno-terrestrial species can tolerate desiccation by entering a metabolically inactive dehydrated state called anhydrobiosis, whereas most species in constantly hydrated habitats, such as freshwater or marine species, cannot undergo anhydrobiosis and are susceptible to desiccation. Although comparative analyses between anhydrobiotic species and desiccation-sensitive species will lead to a better understanding of anhydrobiosis, almost all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Currently, approximately 1200 species have been reported from various habitats, such as marine, fresh-water, or limno-terrestrial environments, though the real number of tardigrade species is estimated to be much higher [ 4 , 5 ]. Tardigrades were found in harsh environments such as Antarctica as well as in urban area, e.g., from activated sludge in a sewage treatment plant [ 6 , 7 , 8 ]. All tardigrades require surrounding water to grow and reproduce, but some limno-terrestrial species are able to tolerate almost complete dehydration.…”
Section: Tardigrades As Model Animals Tolerant To Various Extreme mentioning
confidence: 99%
“…Currently, approximately 1200 species have been reported from various habitats, such as marine, fresh-water, or limno-terrestrial environments, though the real number of tardigrade species is estimated to be much higher [ 4 , 5 ]. Tardigrades were found in harsh environments such as Antarctica as well as in urban area, e.g., from activated sludge in a sewage treatment plant [ 6 , 7 , 8 ]. All tardigrades require surrounding water to grow and reproduce, but some limno-terrestrial species are able to tolerate almost complete dehydration.…”
Section: Tardigrades As Model Animals Tolerant To Various Extreme mentioning
confidence: 99%
“…We have observed that the H. exemplaris embryo hatches in a strictly controlled manner within a short time range (4.03 ± 0.50 days) compared to the wider range observed in R. varieornatus (5.72 ± 1.13 day, see [18]). The small variance in H. exemplaris is similar to the limnic species Isohypsibius myrops [19]. It is worth noting that the R. varieornatus strain YOKOZUNA-1 was derived from a single individual [18], suggesting that genetic variation would not be higher than H. exemplaris , and therefore the hatching time variability is not due to the genetic variability.…”
Section: Discussionmentioning
confidence: 99%
“…TYO ; their morphology was consistent with the descriptions of Paramacrobiotus in the literature [ 47 ]. For breeding, we reared the tardigrade individuals in a thin water layer on 1.2% agar plates at 22°C, and fed them a mixture of algae, Chlorella vulgaris (Chlorella Industry Co., Japan, or Recenttec K. K., Japan), and small monogonont rotifers, Lecane inermis, in a manner similar to that described for other tardigrades [ 48 ].…”
Section: Methodsmentioning
confidence: 99%